Diagnosis of Maths Teaching Efficacy Beliefs Using Expert System - Idha Novianti; Joko Soebagyo; Wildan Toyib (STAI Hubbulwathan Duri, 2023)
Research on the design of an expert system to diagnose Mathematics Teaching Efficacy Beliefs (MTEB) using the Certainty Factor method was the first to be developed. The MTEB instrument was first initiated by Enoch and transformed into an expert system application using the paradigm of modified waterfall software development to sequential or sequential testing steps, ranging from analysis, design, coding, and testing. Data calculation and analysis using the certainty factor method assumes the user's choice is not exact and is at a certain interval. The weighting of expert values from MTEB items is carried out by two experts in the field of mathematics education. Meanwhile, the weight of user consultation uses five approval options, namely strongly agree, agree, simply agree, disagree, and disagree, successively represented by -0.2, -0.1, 0, 0.1, and 0.2. The results of the study gave success to each page of the diagnosis application, and the accuracy rate of the MTEB diagnosis was about 98%. The implication of this research is recommendations for related stakeholders to be followed up so that the MTEB of mathematics teachers becomes even better.